2017
DOI: 10.1101/188847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation and validation of homozygous fluorescent knock-in cells using CRISPR/Cas9 genome editing

Abstract: Gene tagging with fluorescent proteins (FPs) is essential to investigate the dynamic properties of cellular proteins. Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 technology (CRISPR/Cas9) technology is a powerful tool for inserting fluorescent markers into all alleles of the gene of interest and permits functionality and physiological expression of the fusion protein. It is essential to evaluate such genome-edited cell lines carefully in order to preclude off-target effects caused by either (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 51 publications
0
66
0
Order By: Relevance
“…To endogenously tag the condensin I subunit CAP‐D2 and the condensin II subunit CAP‐D3 at the C‐terminus with mEGFP in HeLa Kyoto cells, the paired CRISPR/Cas9 nickase approach was used as described in (Koch et al , ). After selecting GFP‐positive cells by flow cytometry, single‐cell clones were confirmed to be homozygously mEGFP‐tagged at the endogenous locus by PCR, Southern blot and Western blot, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To endogenously tag the condensin I subunit CAP‐D2 and the condensin II subunit CAP‐D3 at the C‐terminus with mEGFP in HeLa Kyoto cells, the paired CRISPR/Cas9 nickase approach was used as described in (Koch et al , ). After selecting GFP‐positive cells by flow cytometry, single‐cell clones were confirmed to be homozygously mEGFP‐tagged at the endogenous locus by PCR, Southern blot and Western blot, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, GFP immunoprecipitation and immunoblotting against all subunits of the condensin complex showed that the formation of pentameric condensin complexes was not prevented by the introduced tag in both asynchronous and nocodazole‐arrested mitotic cell populations. The details of all cell line validation steps are described in Koch et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The CRISPR modified cell lines that we used were heterozygotes with a single allele of the gene edited. There is agreement that some genes (estimated by Koch et al, 2018; to be~25%) cannot tolerate a tag at both loci. It has been reported, for example, that lamin B could be modified at both alleles, but actin cannot (Roberts et al, 2017).…”
Section: Generating Cells With Fluorescent Tags At the Endogenous Lmentioning
confidence: 97%
“…There is agreement that some genes (estimated by Koch et al, 2018; to be~25%) cannot tolerate a tag at both loci. There is agreement that some genes (estimated by Koch et al, 2018; to be~25%) cannot tolerate a tag at both loci.…”
Section: Generating Cells With Fluorescent Tags At the Endogenous Lmentioning
confidence: 99%
“…Heterozygous tagging is sufficient to analyze protein localization and dynamics, but not to quantify protein levels or to verify the functionality of the tagged protein. For experiments that require homozygous edits, other approaches can be used (Koch et al., ; Paquet et al., ).…”
Section: Introductionmentioning
confidence: 99%